2014
DOI: 10.3797/scipharm.1307-03
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, In Vitro Characterization, and In Vivo Pharmacokinetic Evaluation of Respirable Porous Microparticles Containing Rifampicin

Abstract: This study aimed to prepare and evaluate rifampicin microparticles for the lung delivery of rifampicin as respirable powder. The microparticles were prepared using chitosan by the spray-drying method and evaluated for aerodynamic properties and pulmonary drug absorption. To control the drug release, tripoly-phosphate in different concentrations 0.6, 0.9, 1.2, and 1.5 was employed to get a sustained drug release profile. The microparticles were evaluated for drug loading, % entrapment efficiency, tapped density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The key role of these large particles is to avoid being phagocytized by alveolar macrophages because of their large geometric sizes. The deposited particles have an opportunity to release entrapped drugs to the surroundings. , Porous microspheres can be fabricated with the methods of solvent evaporation, spray drying, and supercritical fluid technology . However, these methods have disadvantages such as low encapsulation efficiency, difficulty in removing organic solvents, and of separation particles from the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…The key role of these large particles is to avoid being phagocytized by alveolar macrophages because of their large geometric sizes. The deposited particles have an opportunity to release entrapped drugs to the surroundings. , Porous microspheres can be fabricated with the methods of solvent evaporation, spray drying, and supercritical fluid technology . However, these methods have disadvantages such as low encapsulation efficiency, difficulty in removing organic solvents, and of separation particles from the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the study reported only mild changes in the lung histopathology, suggesting the absence of toxicity after the administration of rifampicin as an inhaled dry powder in rats. In bioavailability studies [ 48 , 73 ], low-dose rifampicin (5–20 mg/kg) was administered via the inhaled route to rats and guinea pigs, which demonstrated up to two-fold higher bioavailability of rifampicin compared to that from the oral route. In the guinea pig study, administration of 20 mg/kg rifampicin as porous particles via the inhaled route led to a relative bioavailability of 0.87 ± 0.33 compared to the intravenous rifampicin (10 mg/kg), while administration of the same via the oral route at 40 mg/kg dose achieved a relative bioavailability of only 0.61 ± 0.23 [ 48 ].…”
Section: Rifampicin: a Long-established Oral Anti-tb Drug With New Po...mentioning
confidence: 99%
“…Porous materials as spherical particles have received a lot of attention lately for the numerous directions in which they can be used, such as in catalytic reactions, separation processes, consumer products (such as water softeners), biomedical devices, coating additives and controlled drug release systems [ 1 , 2 , 3 , 4 , 5 ]. As a polymer matrix, both natural [ 6 , 7 , 8 , 9 , 10 ] and synthetic polymers [ 11 , 12 , 13 , 14 , 15 ] can be used for the synthesis of porous microparticles.…”
Section: Introductionmentioning
confidence: 99%